On some imbedding relations between certain sequence spaces - Mursaleen, M.; Noman, A.K. (Український математичний журнал, 2011)
In the present paper, we introduce the sequence space ` lλp of non-absolute type which is a p-normed space and a BK-space in the cases of 0 < p < 1 and 1 ≤ p < ∞, respectively. Further, we derive some imbedding relations and construct the basis for the space lλp, where 1 ≤ p < ∞. Remove selected Введено поняття простору послiдовностей lλp неабсолютного типу, який є p-нормованим простором i BK-простором у випадках 0 < p < 1 i 1 ≤ p < ∞ вiдповiдно. Крiм того, отримано деякi спiввiдношення вкладення та побудовано базис для простору lλp, де 1 ≤ p < ∞.